Study on chemical composition of the oregano essential oil (Origanum vulgare spp.) from Tacna - Tellez-Monzón, Lena A. (2017)
The oregano essential oil (Origanum vulgare spp.) cultivated in the city of Tacna, Peru, has been chemically analyzed. The physicochemical analysis determined the following characteristics: color (L * 60,51, a * –2,83, b * 14,31), refractive index: 1,475; specific density: 0,9132 and solubility in alcohol: 75 ml. Also, the chemical composition was evaluated by gas chromatography coupled to mass spectrometry. The chromatogram showed the following percentages: l-4 terpineol with 26,56; thymol with 18,80; g-terpinene, 11,77; 2-carene, 6,53; Terpineol, 4,08; M-cymene, 3,27 and carvacrol 2,24, among others present in smaller proportion.